The serve - Elliott, B. (coachesinfo.com)
The success of many players on the men's and women's circuits (eg, Pete Sampras, Richard Krajicek, Mark Philippoussis, Greg Rusedski, Venus Williams or Lindsay Davenport) is at least in part due to their powerful serves. While court surface plays a role in reducing the effectiveness of these serves, a mechanically sound serve should be considered an integral part of all player development. There is no single technique used in the tennis serve, a point that is clearly illustrated by viewing the top professionals. However, critical mechanical features integral to a successful service action are common to the majority of players with an effective serve. It can also be stated that "ineffective service actions" are generally the result of poor development of one or more of these critical features. The general structure used in this discussion may be applied to the power serve along with the slice and kicker serves. The approach I will take with reference to service development is to look at how racket-speed can be developed from "the court-up". Coaches may not always analyse performance in this way, but it is a logical process to follow. Content: Introduction - Preparation - Ball Toss & Leg Drive - The Swing to Impact - Follow Through